GEOMETRIC TRANSFORMATION ON CARVINGS OF TORAJA TONGKONAN HOUSES - Lembang, Suri Toding; Ba’ru, Yusem (MaPan : Jurnal Matematika dan Pembelajaran, 2021)
This research aims to examine the mathematical concepts in traditional Tongkonan houses’ carving and provide information about the meaning of each carving in the Tongkonan house. The research method used is the qualitative research method. The results of the study are obtained by observation and interview. The results showed that it turns out, in some Toraja carvings, contain the concept of transformational geometry, namely reflection. The information also obtained that the carvings in the Tongkonan house are very loaded with meaning, especially about advice, prayer, or hope to all members of the Tongkonan.